Analisis Kepuasan Pengguna E-Learning Di Perguruan Tinggi Menggunakan Model Kano - Rakhmat Safri Agung Pratama; Asif Faroqi; Anita Wulansari (STMIK Banjarbaru, 2022)
UPN Veteran East Java has implemented e-learning as an online learning medium, but no analysis has been carried out to determine the level of user satisfaction in its operation. It is considered necessary to review user satisfaction, so that academic management understands things that need attention to be improved. This study aims to analyze the satisfaction of UPN Veteran e-learning users using the Kano method. The study involved 272 student respondents using e-learning obtained by the Simple Random Sampling method. A total of 29 instrument items, representing 6 analysis variables (Pedagogy, Characteristics, User Interface, Infrastructure, Iteractivity, and Content). Each attribute of the questionnaire is translated into canoe dimensions which have positive statements and negative statements. Furthermore, the classification into the Kano category is carried out by calculating the number of frequencies for each dimension in each attribute, then selecting the dimension with the most frequency. Based on 29 attribute questions, 7 attributes are classified as satisfaction and 14 attributes are classified as dissatisfaction. Attributes that are classified as dissatisfaction (are suggested to get serious attention in improvement, while the attributes of the high satisfaction category are maintained.Keywords: Online learning media; Canoe Dimensions; positive statement; Negative statement Abstrak. UPN Veteran Jawa Timur telah menerapkan e-learning sebagai media pembelajaran online, namun belum dilakukan analisis untuk mengetahui tingkat kepuasan pengguna dalam pengoperasiannya. Dipandang perlu mengkaji kepuasan pengguna, agar manajemen akademik memahami hal-hal yang perlu mendapatkan perhatian untuk ditingkatkan. Penelitian ini bertujuan untuk menganalisis kepuasan pengguna e-learning UPN Veteran menggunakan metode Kano. Penelitian melibatkan 272 responden mahasiswa pengguna e-learning yang diperoleh dengan metode Simple Random Sampling. Sebanyak 29 butir instrumen, mewakili 6 variabel analisis (Pedagogy, Karakteristik, User Interface, Infrastruktur, Iteraktivitas, dan Konten). Setiap atribut kuisioner diterjemahkan ke dalam dimensi kano yang memiliki pernyataan positif dan pernyataan negatif. Selanjutnya dilakukan penggolongan ke dalam kategori Kano dengan cara menghitung jumlah frekuensi tiap dimensi pada setiap atribut, lalu dipilih dimensi dengan frekuensi terbanyak. Berdasarkan 29 atribut pertanyaan, 7 atribut tergolong kepuasan dan 14 atribut yang tergolong ketidakpuasan. Atribut yang tergolong ketidakpuasan disarankan mendapatkan perhatian serius dalam perbaikan, sedangkan atribut kategori kepuasan yang tinggi tetap dipertahankan.Kata kunci: Media pembelajaran online; Dimensi Kano; Pernyataan positif; Pernyataan negatif